Evaluating Momentum and Contrarian Strategies For Technology Stocks During Excessive Speculation - Simlai, Pradosh (Indian Journal of Finance, 2009)
Momentum and contrarian returns have been documented by a large number of studies. In this paper we investigate the performance of technology stocks by using these two widely followed investment strategies during a speculative boom period. We discuss the effectiveness of various long and short trading strategies for a well balanced sample of technology stocks and find that by executing a simple buy bottom strategy, a technology investor could take advantage of the overreactions in order to generate higher returns during the period of excessive speculation. We also show that accounting for conditionally heteroskedasticity increases the evidence that risk adjusted returns are strongly related to market betas of a benchmark return and NASDAQ composite index returns.